The professional image of a nurse as seen by parents of children hospitalized in the oncology department - Wańkowicz, Agnieszka; Bednarek, Anna; Golubka, Ivan; Golubka, Kristiana; Wańkowicz, Piotr; Mierzyński, Radzisław; Golubka, Wiktoria; Dłuski, Dominik; Golubka, Paweł; Darmochwał-Kolarz, Dorota (Polish Journal of Public Health, 2016)
Introduction. The professional image of a nurse which is influenced by a whole variety of factors is the main subject of this work. The social attitudes toward nurses are related to people’s own beliefs, opinions, stereotypes, as well as the nurses’ professional, personal and interpersonal skills. The proper image of a nurse is very important. Patients are becoming increasingly demanding toward nurses which poses new challenges for nurses attempting at creating a positive image of this profession. Aim. The aim of this work was to elicit the opinions about nurses’ work from parents of children hospitalized on the oncologic ward.Material and methods. The authors used a questionnaire of their own making and conducted a literature analysis. The literature review was made using the data taken from Main Medical Library. The research group consisted of 50 parents of children hospitalized in Oncology, Hematology and Child Transplantology Department in Lublin. All the parents were advised about the aim of the study and informed that the questionnaire is anonymous and voluntary. The obtained results have then undergone a statistical analysis, using a Chi2 test. Statistical significance was reached at the level of p